Psychotropic medication use for paediatric mental health patients in an emergency department. (30th September 2020) - O'Donnell, Sinead M; Carison, Anna; Hill, Ashley; Say, Daniela; Hiscock, Harriet; Babl, Franz E
Abstract: Objective: There is paucity of evidence for psychotropic medication use in children and adolescents presenting with mental health (MH) problems to the ED. We set out to describe paediatric psychotropic medication use in the ED. Methods: We conducted a retrospective electronic medical record review of ED patients with MH discharge codes at a tertiary paediatric ED in 2018. We assessed the epidemiology and management of patients who received a psychotropic medication. We calculated the odds ratios (ORs with 95% confidence intervals [CIs]) of key demographic factors of medicated versus non‐medicated MH patients. Results: During 2018 there were 1695 MH‐related presentations to the ED. Of these, 280 presentations resulted in the patient receiving a psychotropic medication (16.5%). Medicated children with MH illness were more likely to be male (OR 1.50, 95% CI 1.16–1.96), have a more acute triage category (OR 3.37, 95% CI 2.28–4.98), have an ED length of stay greater than 12 h (OR 3.96, 95% CI 2.56–6.13) and present after hours (OR 1.51, 95% CI 1.16–1.96). Most had a diagnosis of acute behavioural disturbance or suicidal ideation. A variety of treatment regimens were used but children primarily received a single oral agent (diazepam or olanzapine). Parenteral medications were given in 8.6%. No adverse events were recorded. Conclusion: A minority of children with MH presentations to the ED were medicated. It will require multicentre research to determine the most effective and safe acute psychotropic agents for oral and parenteral use in children in the ED. Abstract : Relatively few children and adolescents with mental health presentations receive psychotropic medications in ED. Those who did were likely to be male, have a more acute triage category (Australasian Triage Scale category 1 or 2), have an ED length of stay greater than 12 h and present after hours.